UPAYA KEPOLISIAN DALAM MELAKUKAN PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA KEKERASAN SEKSUAL PADA ANAK (PEDOFILIA) (STUDI KASUS DI POLRES BULELENG - Putu Hadi Hendra Tanu Sudibya; Made Sugi Hartono; I Wayan Landrawan (Jurnal Ilmu Hukum Sui Generis, 2023)
This research aims to (1) To find out and analyze the process of law enforcement at the police level regarding criminal acts of sexual violence against children in the jurisdiction of the Buleleng Police Station (2) To find out and analyze how the police make efforts to deal with the perpetrators of criminal acts of sexual violence against children. in the jurisdiction of the Buleleng police station. In this research, the type of research used is empirical legal research using descriptive research characteristics. The data and data sources used are primary data and secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data collection techniques used are document study techniques, observation techniques and interview techniques. The sampling technique used was a non- probability sampling technique and the subject determination used a purposive sampling technique. Next, the data obtained is processed and analyzed qualitatively. The results of this research show (1) The law enforcement process in dealing with this is the Women and Children Services Unit, the Criminal Investigation Unit of the Buleleng Regency Police, in an effort to resolve criminal acts of sexual violence against children through In its implementation the police provide a place for mediation, communication and discussion. between the Reporter or Victim and the Reported Party, officers only take action in the form of listening to the wishes of the reporter and the reported party, carrying out the legal process even if there is peace. (2) Efforts to overcome criminal acts of sexual violence against children in Buleleng Regency carried out by the Buleleng Police, namely repressive (penal) efforts carried out by the Buleleng Police, namely by carrying out inquiries or investigations in accordance with applicable legal provisions, carrying out all kinds of actions according to procedures. not handling cases selectively, and handling cases of public attention professionally and proportionally.